PENDAMPINGAN TERHADAP GURU DALAM MENERAPKAN METODE PEMBELAJARAN YANG EFEKTIF DAN INOVATIF DALAM MENARIK MINAT BELAJAR SISWA DI MI NASRUL ULUM KLAGENSRAMPAT PADA MASA PANDEMI COVID-19 - Ida Latifatul Umroh; Khotimah Suryani; Ita Hidayatus Sholihah; Krisna Andika; Rihlatulillah Rihlatulillah (LP2M Universitas Ibrahimy, 2021)
The purpose of this activity is for increasing students interest in learning at MI Nasrul Ulum Klagensrampat. This activity uses a learning method in conveying material to students.By applying this method the writer hopes that the learning process can be achieved properly. Therefore, it is very important for educators to recognize several kinds of learning methods so that students feel happy and comfortable when learning takes place. The writing of this work were supported by the researcher’s activity after doing identification and communication with the teacher, so that the researchers and the teacher were able to find out the obstacles faced by the students in teaching and learning activity which has been done. In this activity, the researcher applied various methods of effective and innovative teaching which were able to increase students learning interest. The learning methods are puzzle method, flashcard method, silent way method, make a match method, snowball method, bamboo method, and monopoly method